FAKTOR MEMPENGARUHI PERILAKU KECANDUAN SOSIAL MEDIA - Khatimah, Khusnul; Irawan, Donny Taufik Ryan (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
Social media is a digital platform product that has received a positive response from people. Social media is no longer part of tertiary or primary needs but secondary needs. For users, social media has become part of their daily lives, and teenagers to young adults are the largest group of users, causing addictive behavior towards their users. Addiction to social media can be influenced by several factors such as psychosocial. Many researchers use the cross-sectional method in their research. This systematic review aims to analyze 12 international journals regarding the factors that influence social media addiction, and psychosocial (depression, anxiety, FoMO, and so on) are reported to have the most influence on social media addiction. The other variables are bullying, cyberbullying, self-esteem, and cultural influence. Types of social media addiction used in educational research are associated with decreased academic achievement due to poor sleep quality. The aspects of social media addiction are emotional, behavioral, affective, and cognitive. These findings provide recommendations for conducting more experimental research related to social media addiction in students.